PROYEKSI RASIO KINERJA KEUANGAN BANK SYARIAH YANG AKAN MELAKUKAN MERGER STUDI PADA PT BRIS, PT BNIS DAN PT BSM DARI TAHUN PELAPORAN 2015-2019 - Ulfah Nofitasari; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to calculate the projected financial performance after  merger. This merger is expected to become one of the components to support long-term development in 2005-2025, as one of the major banks providing funds for government development. This merger is also expected to be able to form a new bank that can be categorized as a book 4 bank with a core capital ownership of more than 30 trillion by 2025. The researcher uses the independent variable in the form of mergers and the dependent variable in the form of financial performance. Fundamental financial performance is measured by using financial ratios which are represented by 4 ratios namely market value ratio, profitability ratio, liquidity ratio, and leverage. Researchers used 6 measuring variables. Market value ratio is represented by PBV (Price Book Value) Profitability ratio is represented by ROA (Return On Assets), ROE (Return On Equity), and NPM (Net Profit Margin), liquidity ratio is represented by CR (Current Ratio), and leverage is represented by DER (Debt to Equity Ratio). This study uses quantitative research by taking data from the official website of each bank. This sample uses 3 banks that have merged, there are PT BRIS, PT BNIS and PT BSM. The data analysis technique uses Holt's linear exponential smoothing method. The results showed that the projected stock price was in the expensive category. While the projection of the liquidity ratio has a good trend of development. However, the projection of profitability and leverage shows the opposite trend.